Streptococcus pneumoniae meningitis in Alberta pre- and postintroduction of the 7-valent pneumococcal conjugate vaccine - Jennie Johnstone; Gregory J. Tyrrell; Thomas J. Marrie; Sipi Garg; James D. Kellner; the Streptococcus pneumoniae Alberta Team (SPAT) group (Canadian Journal of Infectious Diseases and Medical Microbiology, 2011)
The objective of this study was to describe the epidemiology, clinical characteristics, microbiology and outcomes of patients of all ages with Streptococcus pneumoniae meningitis between 2000 and 2004; two years pre- and postintroduction of an S pneumoniae 7-valent conjugate vaccine program in Alberta in children younger than two years of age. The high mortality rate associated with S pneumoniae meningitis, despite appropriate therapy, suggests that prevention of S pneumoniae meningitis is critical. Despite implementation of a PCV-7 program in Alberta, rates of S pneumoniae meningitis in children younger than two years of age is still high. Thus, continued research into safe and efficacious vaccines covering a broader range of S pneumoniae serotypes is necessary.